Pierre Robbins Syndrome - Imran, Muhammad; Khan, Faiz Muhammad; Rehman, Sajjad ur (Journal of Postgraduate Medical Institute, 2011)
Pierre Robbins Syndrome, a not uncommon congenital anomaly, is diagnosed by the clinical triad of micrognathia, glossoptosis and cleft palate. When associated with other syndromes, it is called Robbins anomaled. Certain associated anomalies in our patient have not previously been described with the syndrome. Management of infant s with this syndrome, though difficult and painstaking, is nonetheless rewarding.